ANTIBACTERIAL EFFICACY OF GRAPE SEED EXTRACT CONTAINING 2.9% TANNIN AGAINST ENTEROCOCCUS FAECALIS BIOFILM - SOETANTO, SHELVY; SUPRASTIWI, ENDANG; ASRIANTI, DINI (International Journal of Applied Pharmaceutics, 2019)
Objective: The aim of this study was to observe the antibacterial efficacy of grape seed extract (GSE) against Enterococcus faecalis biofilm. Methods: A biofilm of E. faecalis American Type Culture Collection (ATCC) 29212 strain was prepared using sterile cellulose nitrate filter membrane incubated on brain heart infusion agar at 37°C for 72 h under aerobic condition. Each membrane containing E. faecalis biofilm was added to three tubes of phosphate-buffered saline (control), three tubes of GSE, and three tubes of 2% clorhexidine. The number of viable DNA cells was measured using real-time polymerase chain reaction. The data were statistically analyzed using non-parametric Kruskal–Wallis test and Mann–Whitney U-test. Results: GSE had antibacterial efficacy against E. faecalis biofilm. The difference in the amount of E. faecalis DNA between all groups was statistically significant (p=0.05). Conclusion: GSE has antibacterial efficacy against E. faecalis biofilm.